A PC-based Flexible Solution for Virtual Instrumentation of a Multi-Purpose Test Bed - Kozek, Martin; Christian, Bilik; Christian, Benatzky (International Journal of Online and Biomedical Engineering (iJOE), 2006)
The aim of the paper is to give an overview of a test bed set up for lightweight flexible structures. The purpose of the test bed is to compare different concepts for suppressing structural vibrations. It is demonstrated that such a complex measurement and actuation task can be easily implemented on a single PC using standard software like Matlab/SIMULINK® with a minimum of custom hardware. With the help of this PC standard engineering tasks like measuring, identification of transfer functions, as well as controller design and implementation in soft real-time can be carried out easily (rapid prototyping). The resulting system is flexible and scalable, enabling an engineer to perform all the above mentioned tasks for a given test object within minimum time. Additionally, the utilization of Matlab/SIMULINK® facilitates the realization of a versatile virtual instrumentation system which is easy to use and may also be remote-controlled.